Physiotherapists and Osteopaths' Attitudes: Training in Management of Temporomandibular Disorders - Stefano Saran; Sabina Saccomanno; Maria Teresa Petricca; Andrea Carganico; Salvatore Bocchieri; Rodolfo Francesco Mastrapasqua; Elena Caramaschi; Luca Levrini (MDPI AG, 2022)
Temporomandibular disorders (TMDs) are a condition which has multifactorial etiology. The most acknowledged method to classify TMDs is the diagnostic criteria (DC) introduced firstly by Dworkin. This protocol considers different aspects that are not only biological, but even psychosocial. Diagnosis is often based on anamnesis, physical examination and instrumental diagnosis. TMDs are classified as intra-articular and/or extra-articular disorders. Common signs and symptoms include jaw pain and dysfunction, earache, headache, facial pain, limitation to opening the mouth, ear pain and temporomandibular joint (TMJ) noises. This study regards two kind of clinicians that started in the last years to be more involved in the treatment of TMDs: osteopaths (OOs) and physiotherapists (PTs). The purpose is to analyze their attitude and clinical approach on patients affected by TMDs. Four hundred therapists answered an anonymous questionnaire regarding TMJ and TMDs. OOs showed greater knowledges on TMDs and TMJ and, the therapists with both qualifications seemed to be most confident in treating patients with TMDs. In conclusion this study highlights OOs and all the clinicians with this qualification, have a higher confidence in treating patients with TMD than the others. Dentists and orthodontists, according to this study, should co-work with OOs and PTs, because they are the specialists more requested by them than other kinds of specialists.